Дорога в Россию :учебник русского языка : первый уровень -- 1 /В.Е. Антонова, М.М. Нахабина, А.А. Толстых; [Antonova, M M Nakhabina, A A Tolstykh]. - Antonova, V. E.
Sách chương trình cử nhân Ngôn ngữ Nga.